FILSAFAT MENGAJARI MANUSIA BERPIKIR KRITIS - Rosichin Mansur (Universitas Islam Malang, 2019)
Humans as thinking, of course in thinking can not be separated from the activities of thinking. Critical thinking or critical thinking is something that everyone must have. With critical thinking a person will not slip into the abyss of negativity, and falsehood because critical thinking is positive thinking to achieve the product of truth and clarity. Critical thinking is essentially not the monopoly of adults, madrasa or school children also have room for critical thinking even though the level of criticality is different from adults. Philosophy teaches humans to think critically and even deeply. Cogito Descartes is one method used to teach someone to think critically, starting from a doubt to a certainty.